Based on improved malthusian model microblogging topic trend forecast - Yan-xiang HE; Jian-bo LIU; Nan LIU; Min PENG; Qiang CHEN; Jing HE (Tongxin xuebao)
Although trend forecasting problem is the research focus of social computing，yet the topic trend forecast of micro logging platform is still at the exploratory stage.Based on the analyzing，extracting and defining the influencing factors of the trends of event，the improved Malthus model，which is more applicable to solve microblogging topic trend forecast problem is presented.Then the model is mapped to the neural network，and the genetic algorithms are used to predict the trend of events.Experiments show that this method can predict the trend of long-term events in the social network with good results，and can predict the outbreak point and posting volume effectively.It is worth nothing that the method is also suitable for small sample forecasting problems.